2012
DOI: 10.1007/s00404-012-2685-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of surgical failure following sacrospinous colpopexy for the treatment of uterovaginal prolapse

Abstract: The presence of advanced anterior vaginal wall prolapse, prior vaginal repair and a lack of mesh augmentation of the anterior compartment are significant risk factors for the surgical failure of sacrospinous suspension surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Previous studies have reported anatomic success rates of 77–94% after monolateral SF in smaller cohorts of VVP first recurrence [ 24 26 ]. Several authors [ 27 29 ] have described 10%–30% anterior support defects after sacrospinous fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported anatomic success rates of 77–94% after monolateral SF in smaller cohorts of VVP first recurrence [ 24 26 ]. Several authors [ 27 29 ] have described 10%–30% anterior support defects after sacrospinous fixation.…”
Section: Discussionmentioning
confidence: 99%
“…This high recurrence could be explained by the deviation in vaginal axis caused by unilateral stitch placement or due to damage to neurovascular support . Non‐placement of anterior mesh is another risk factor and a Cochrane review proposed that use of mesh or graft at anterior colporaphy may reduce the risk of anterior prolapse . Six of our women in the SSHP group with recurrent cystocele had concomitant anterior repair and cannot be considered as de novo cystoceles.…”
Section: Discussionmentioning
confidence: 67%
“…These discrepant findings may be attributed to heterogeneity among the studied women, variable definitions of failure and potential differences in the concerned compartment in which failure was described . In some studies, women with preoperative stage 3 or 4 were not included, since this was considered a risk for surgical failure . Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, indirect data for the posterior compartment are available from randomized trials of patients with multicompartment prolapse, where restoration of apical support was the primary outcome. Τhe 2016 Cochrane systematic review and meta-analysis [18] summarized the results of three trials [40–42] of apical prolapse repairs, with optional concomitant anterior/posterior repairs, where follow-up data on the posterior compartment were reported. Data showed no statistically or clinically significant difference in objective failure rates in the posterior compartment between mesh and no mesh repairs of multicompartment prolapse: failure rate was 7.4% (8 of 107 repairs) with mesh repairs compared to 11.7% (14 of 119 repairs) with native tissue repairs ( p  = 0.92).…”
Section: Resultsmentioning
confidence: 99%